Tale of two Indians: Heterogeneity in type 2 diabetes pathophysiology. Issue 8 (29th July 2019) - Staimez, Lisa R.; Deepa, Mohan; Ali, Mohammed K.; Mohan, Viswanathan; Hanson, Robert L.; Narayan, K.M. Venkat
Abstract: Aims: Type 2 diabetes is a heterogeneous disease and may manifest from multiple disease pathways. We examined insulin secretion and insulin resistance across two ethnicities with particularly high risk for diabetes yet with widely different distributions of weight class. Materials and Methods: In this population‐based, cross‐sectional study, Pima Indians from Southwestern United States (n = 865) and Asian Indians from Chennai, India (n = 2374) had a 75‐g oral glucose tolerance test. We analysed differences in plasma glucose, plasma insulin, insulin resistance (HOMA‐IR), and insulin secretion (ΔI0‐30 /ΔG0‐30 ) across categories of body mass index (BMI) and glycemic status per American Diabetes Association criteria. Results: Pima Indians were younger (mean 27.4 ± SD 6.6, Asian: 33.9 ± 6.7 years) and had higher BMI (33.6 ± 8.1, Asian: 25.7 ± 4.9 kg/m 2 ). Among normal weight participants (mean BMI: Pima 22.4 SE 0.2; Asian 22.2 SE 0.06 kg/m 2 ), fasting glucose was higher in Asian Indians (5.2 vs Pima: 4.8 mmol/L, P  = .003), adjusted for age and sex. Pima Indians were three times as insulin resistant as Asian Indians (HOMA‐IR: 7.7 SE 0.1, Asian: 2.5 SE 0.07), while Asian Indians had three times less insulin secretion (Pima: 2.8 SE 1.0 vs Asian: 0.9 SE 1.0 pmol/mmol), a pattern evident across age, BMI, and glycemic strata. Conclusions: Metabolic differences between Pima and Asian Indians suggest heterogeneous pathways of type 2 diabetes in the early natural history of disease, with emphasis of insulin resistance in Pima Indians and emphasis of poor insulin secretion in Asian Indians.